2017
DOI: 10.1182/blood-2016-04-709584
|View full text |Cite
|
Sign up to set email alerts
|

A novel humanized mouse model with significant improvement of class-switched, antigen-specific antibody production

Abstract: • Human IL-6 improves T-cell engraftment and serum IgG production in humanized mice.• IgG-switched memory B cells in IL-6 knock-in mice displayed a diverse antibody repertoire and high specificity against immunized antigen.Humanized mice are a powerful tool for the study of human hematopoiesis and immune function in vivo. However, the existing models cannot support robust adaptive immune responses, especially the generation of class-switched, antigen-specific antibody responses. Here we describe a new mouse st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
94
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(105 citation statements)
references
References 42 publications
5
94
1
Order By: Relevance
“…The addition of human Il6 gene knock‐in has demonstrated improved haematopoiesis, class switching and a high frequency of somatic hypermutation …”
Section: Humoral Immunity In Humanized Micementioning
confidence: 99%
See 1 more Smart Citation
“…The addition of human Il6 gene knock‐in has demonstrated improved haematopoiesis, class switching and a high frequency of somatic hypermutation …”
Section: Humoral Immunity In Humanized Micementioning
confidence: 99%
“…15,59 The addition of human Il6 gene knock-in has demonstrated improved haematopoiesis, class switching and a high frequency of somatic hypermutation. 26 Due to this, a further advancement of the MISTRG mouse was created, with the addition of the human Il6 by gene knock-in, resulting in the new MISTRG-6 strain. 26 This new model shows improved B-cell and malignant plasma cell development, to investigate their effects on lytic bone disease, however, this strain is yet to be used in the context of infectious disease.…”
Section: Humoral Immunity In Humanized Micementioning
confidence: 99%
“…Studies using sera from DENV immunized IL6 transgenic BLT NSG mice also showed improved IgG responses compared to BLT NSG mice (unpublished data). A recent report suggests that IL6 knock-in mice had improved class-switched memory B cells and ovalbumin specific IgG in response to immunization with OVA [35]. …”
Section: Improving B Cell and Antibody Responses In Humanized Blt Nsgmentioning
confidence: 99%
“…Thus, mice expressing human cytokines, including a combination of SCF, GM-CSF, and IL-3 (NSG-SGM3) or M-CSF, IL-3, GM-CSF, and thrombopoietin (MISTRG) show improved myelopoiesis 7, 8 . Mice carrying a knock-in of human IL-6 show improved B-cell development and function 9 .…”
Section: Introductionmentioning
confidence: 99%